Technical Efficiency Differential of Groundnut Production in Jigawa State, Nigeria - G.Z, REKWOT; M A, DAMISA; O, YUSUF (Journal of Management and Science, 2013)
This study was undertaken to principally determine the technical efficiency differential of groundnut production by adopters and non-adopters of Institute for Agriculture (IAR) groundnut varieties in Jigawa state, Nigeria.Interview schedule was used to collect data from a sample of 227 respondents who were selected randomly from the four agricultural zones in the study area. The analytical tools employed in data analysis include descriptive statistics and stochastic frontier production function. The result of the Maximum Likelihood Estimation of the stochastic frontier production function revealed that the maximum, minimum and mean efficiencies of farmers who adopted IAR groundnut varieties were 91%, 18% and 70% respectively while in the case of farmers who did not adopt, the maximum, minimum and mean efficiencies were 88%, 18% and 63%. This implies that the farmers who adopted IAR groundnut varieties are more technically efficient than farmers who did not adopt IAR groundnut varieties. Therefore, adopting of IAR groundnut varieties by farmers can contribute in enhancing their technical efficiency.The sources of technical inefficiency of adopters of IAR groundnut varieties were age (P<0.01), family size (P<0.01), education (P<0.01), extension (P<0.01) and credit(P<0.05). The result of the inefficiency model of the non-adopters of IAR groundnut varieties revealed that the major factors influencing the technical inefficiency were family size (P<0.01), education (P<0.01), farming experience (P<0.05) and extension contact (P<0.05). Based on the findings of the study, Based on the findings of the study, it is recommended that Government should fast track seed multiplication and distribution through effective extension service delivery to farmers so as to intensify and sustain the adoption of improved groundnut varieties towards enhancing the technical efficiency of groundnut farming households.